Use of Counting Media to Improve Understanding of Elementary School Students - Fitriyani Fuji Lestari; Rasilah Rasilah (MASI Mandiri Edukasi, 2025)
Counting media in elementary school mathematics learning has proven effective in enhancing students' understanding of fundamental mathematical concepts. This study aimed to explore the impact of counting media on students' conceptual understanding, learning motivation, and the challenges associated with its implementation. Utilizing a qualitative descriptive approach, data were collected through classroom observations, teacher interviews, focus group discussions, and document analysis. The findings reveal that counting media, such as counting blocks, coins, and number boards, significantly improved students' ability to visualize and comprehend abstract mathematical concepts, resulting in a 20% increase in average test scores. Counting media fostered active student participation and boosted motivation, making learning more engaging and enjoyable. Teachers also reported that these tools facilitated more varied and effective instructional strategies. Despite its benefits, the implementation of counting media faced challenges, including limited access to resources in rural areas and insufficient teacher training. Addressing these challenges requires more substantial support from schools and governments, including resource provision and professional development programs. Overall, this study underscores the potential of counting media to enhance cognitive outcomes and foster positive learning attitudes and collaboration among students. The results suggest that integrating innovative media into mathematics education can significantly improve the quality of learning, providing valuable insights for broader educational reforms.